AN IN VITRO EXPERIMENTAL INVESTIGATION OF THE ANTIBACTERIAL, ANTIOXIDANT, AND THERAPEUTIC EFFICACY OF ACACIAMANGIUM BARK EXTRACTION AGAINST Haemonchuscontortus INFECTION - Tekad Urip Pambudi Sujarnoko; Dwi Budiono; Novia Amalia Sholeha; Ridwan Siskandar; Theo Mahiseta Syahniar; Mira Andriani; Anis Usfah Prastujati; Anggra Fiveriati; Mohammad Miftakhus Sholikin (Journal of Animal and Plant Sciences, 2026)
The significant economic losses in the small ruminant sector caused by Haemonchuscontortus highlight the urgent need for alternative therapeutic solutions. These alternatives should not only be environmentally sustainable but also prevent the development of resistance, with Acaciamangium emerging as a potential option. The study aimed to evaluate the efficiency of A. mangium bark extract against adult H. contortus and to assess its antibacterial and antioxidant properties using hot water extraction method. The extraction process used a factorial completely randomized design with three temperatures (40, 60, and 80℃) and two durations (45 and 60 minutes). The concentrations of phenols, tannins, and condensed tannins were measured, along with antioxidant (DPPH scavenging) and antibacterial activities. The anthelmintic efficacy was compared to albendazole over a seven-hour period. Result: Extraction at 80℃ significantly increased the concentration of phenols, tannins, tannin-to-phenol ratio, and condensed tannins compared to lower temperatures (P ≤ 0.01). A 60-minute duration yielded higher levels of bioactive compounds than 45 minutes (P ≤ 0.01). The strongest DPPH activity occurred at 40°C for 60 minutes (P ≤ 0.05). The 100% and 75% extract concentrations showed comparable anthelmintic activity to albendazole after seven hours. The extract also demonstrated significant antibacterial activity, producing larger inhibition zones than the control (P ≤ 0.01). Conclusion: Hot water extract of A. mangium bark exhibits potent anthelmintic, antioxidant, and antibacterial activities, support its potential as a natural agent for parasite control in small ruminants. Recommendation: Further invivo studies are recommended to confirm the efficacy, safety, and potential integrity of the extract in small ruminant health practices.
Keywords: Antioxidant compounds; condensed tannins; gastrointestinal nematodes; high-temperature plant extraction; phenolic compounds; small ruminants